"Belt and braces approach; added benefit and … extra reassurance": a multi-stakeholder examination of the challenges to effective provision of pre-exposure prophylaxis (PrEP) for HIV prevention among men who have sex with men (MSM) in Northern and Central England. Issue 6 (3rd June 2021) - Hillis, Alyson; Germain, Jennifer; Hibbert, Matthew Peter; Hope, Vivian; Van Hout, Marie Claire
ABSTRACT: Pre-exposure prophylaxis (PrEP) involves HIV negative individuals taking antiretroviral drugs to reduce the probability of infection if exposed and is available through the IMPACT trial in England. This study aimed to explore men who have sex with men (MSM) and service provider (SP) perspectives on provision and accessibility of PrEP in Northern and Central England. Twenty MSM and 25 SPs from four Northern cities and one city in the West Midlands region were recruited for semi-structured interviews (December 2018 to October 2019). Interviews were analysed using Interpretative Phenomenological Analysis (IPA). Three key themes emerged: "Self-sourcing PrEP"; "Service delivery learnings"; and "Impact of using PrEP". Problems with equity of access and accessibility were noted, and recommendations for the future of PrEP programming and equitable service delivery were also presented. The study highlighted divergence in PrEP service experience from patients and providers, with results informing policy, practice and professional training.